Coming Full Circle: Thirty Years of Paediatric Fluid Resuscitation. Issue 3 (May 2017) - Glassford, N. J.; Gelbart, B.; Bellomo, R.
Fluid bolus therapy (FBT) is a cornerstone of the management of the septic child, but clinical research in this field is challenging to perform, and hard to interpret. The evidence base for independent benefit from liberal FBT in the developed world is limited, and the Fluid Expansion as Supportive Therapy (FEAST) trial has led to conservative changes in the World Health Organization–recommended approach to FBT in resource-poor settings. Trials in the intensive care unit (ICU) and emergency department settings post-FEAST have continued to explore liberal FBT strategies as the norm, despite a strong signal associating fluid accumulation with pulmonary pathology in the paediatric population. Modern clinical trial methodology may ameliorate the traditional challenges of performing randomised interventional trials in critically ill children. Such trials could examine differing strategies of fluid resuscitation, or compare early FBT to early vasoactive agent use. Given the ubiquity of FBT and the potential for harm, appropriately powered examinations of the efficacy of FBT compared to alternative interventions in the paediatric emergency and ICU settings in the developed world appear justified and warranted.